Anisotropy Effect of Masonry on the Behaviour and Bearing Capacity of Masonry Walls - M. Smilović Zulim; J. Radnić (Advances in Materials Science and Engineering)
Firstly, an updated numerical model for the numerical analysis of planar unreinforced and confined masonry walls is presented. The model can simulate the main nonlinear material effects of masonry and reinforced concrete. A simplified anisotropic constitutive model for masonry is developed and presented. The criteria for the limit bearing capacity and collapse of masonry are separately defined for normal stresses only and for normal and shear stresses. The presented numerical model is verified and used to analyse the anisotropy effect of masonry on the behaviour of unreinforced and confined two-story anisotropic masonry walls with different coefficients of anisotropy, wall lengths, and quality of masonry under horizontal static forces. The influence of the anisotropy coefficient of the masonry on the response of the walls is discussed in detail, and the main conclusions are given.